Subcutaneous adipose tissue surgery - Fossati, Guillermo (Cirugía del Uruguay, 1991)
Classical subcutaneous adipose tissue resection techniques (lipectomies and dermolipectomies) and grafts of the same tissue are analysed. The essential advance obtained with liposuction and fat-injection graft is explained. The importance of body form among cosmetic requirements of present times and the way in which these new techniques contribute to improve the condition of patients that need this type of corree/ion are mentioned